A Hybrid Online and Offline Approach to Teaching Spoken English Based on Modern Educational Technology. (30th June 2022) - Xiaodong, Li
Abstract : People nowadays care more about the source and outcome of English instruction, resulting in an improvement in the quality of English instruction. As a result, the majority of students' reading and writing levels increase steadily, but their listening ability does not, resulting in an extremely unbalanced development of the "listening, reading, and writing" four skills. The use of language in real-world situations is a reflection of human creativity, and the content and tone of the same speaker's speech at different times, places, and occasions can vary significantly. Language usage cannot be separated from its context. This study proposes a hybrid online and offline English speaking teaching method based on modern educational technology. The method transforms offline teaching materials into a suitable context to create a rich and diverse online speaking classroom. This new teaching method constructs a teaching platform with online and offline as the primary subjects, replacing the previous single mode of teacher output and passive student input to form an all-round teaching platform distinguished by systematization, standardization, all-round language training, high intensity, accuracy, and fluency in language output. The experimental results demonstrated that our evaluation results are useful for providing feedback on the quality of teaching and promoting learning outcomes.